Project Report on Implementation of Digital Data Scrambler and Unscrambler - SUSHIL CHANDRAN, DEEPAK JOSEPH, NIKESH P MATHEW and RAJESH GOPINATH (2000)
INTERNAL GUIDE:A A SHOLAPUR, MVJCE EXTERNAL GUIDE:D N RENJIH
Keywords: Implementation of Digital Data Scrambler and Unscrambler